2020
DOI: 10.1038/s41598-020-72405-9
|View full text |Cite
|
Sign up to set email alerts
|

The oil removal and the characteristics of changes in the composition of bacteria based on the oily sludge bioelectrochemical system

Abstract: Microbial fuel cell (MFC) technology is a simple way to accelerate the treatment of the oily sludge which is a major problem affecting the quality of oil fields and surrounding environment while generating electricity. To investigate the oil removal and the characteristics of changes in the composition of bacteria, sediment microbial fuel cells (SMFCs) supplemented with oily sludge was constructed. The results showed that the degradation efficiency of total petroleum hydrocarbon (TPH) of SMFC treatment was 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Typically, an oily sludge is composed of 40−52% alkanes, 28− 31% aromatics, 15−32% asphaltenes, and colloids. 4 At present, the organic solvents used for the oil component extraction mainly include chloroform, dichloromethane, chloroform, acetone, n-hexane, and n-heptane. In particular, n-heptane has the extraction effect on all components.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, an oily sludge is composed of 40−52% alkanes, 28− 31% aromatics, 15−32% asphaltenes, and colloids. 4 At present, the organic solvents used for the oil component extraction mainly include chloroform, dichloromethane, chloroform, acetone, n-hexane, and n-heptane. In particular, n-heptane has the extraction effect on all components.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1,3 The ecological environment was seriously threatened by the presence of oily sludge, and oil resources were wasted. 4 The oil phase in oily sludge is mainly crude oil, which is mainly composed of hydrophobic petroleum hydrocarbons (PHCs) (e.g., saturated hydrocarbons, aromatic hydrocarbons, colloids, and asphaltenes). Asphaltenes and colloids have the greatest viscosity and the lowest liquidity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…n-Alkanes can breakdown through demethylation, a process where a terminal methyl group is cleaved and replaced with a hydrogen atom. Demethylation of n-alkanes occurs naturally through microbial degradation and can affect the organic chemistry of oil and gas (Guo et al 2020). The loss of methyl groups results in artificially low CPI values that do not accurately represent the initial organic material composition.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al. showed that the oily sludge is suitable for SMFC operation, with a maximum output voltage of 299.13 mV. , However, a key issue that currently limits the practical application of SMFCs is the low power generation efficiency. There are many limiting factors influencing internal resistance. The cathode, anode, pH, appropriate catalysts (activated carbon, cobalt-nitrogen framework), and external resistance are important limiting factors for the performance of the MFC. Among the many factors that affect its electricity production, the anode is considered to be a key factor because it affects the microorganism growth and metabolism of full stop.…”
Section: Introductionmentioning
confidence: 99%